COMPARATIVE STUDY OF AL-GHAZALI'S THINKING AND ZAKIAH DARADJAT'S IN ISLAMIC EDUCATION CURRICULUM - Rateh Ninik Pramitasary (Hunafa: Jurnal Studia Islamika, 2019)
This research focuses with the view of the curriculum from Islamic thinkers, Al-Ghazali and Zakiah Daradjat. Both are compared to find out the meeting point of similarities and differences in compiling Islamic Education curriculum. The research process uses qualitative methods. Research with qualitative nature is descriptive and is a literature study that prioritizes a lot of reading in the library. The research objective is to explain the view of the Islamic curriculum according to Al-Ghazali, the view of the Islamic curriculum according to Zakiah Daradjat, as well as their differences and similarities. Al-Ghazali in the book Ihya 'Ulumuddin revealed that there are three aspects namely mental development, intellectual education, physical education. Zakiah Daradjat in the book of Islamic Education revealed that the Islamic Education curriculum must contain seven aspects, namely physical education, sense education, faith education, moral education, psychology education, beauty education, and social education.